The Development of Student Worksheet Based on Virtual Laboratory to Train Scientific Attitude on Photosynthesis Materials - Fatimah, Nurul Izzah; Isnawati, Isnawati (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2024)
Photosynthesis is a material that can be verified so it becomes the right choice to have a practical activities. Based on a survey on class XI MIPA and XII MIPA at SMAN 8 Surabaya, it was found that 89.5% of them had never carried out real practicum activities. In addition, one of the factors causing the low of practicum activities is because teachers having difficulties in compiling practicum guides. This causes the scientific attitude of students getting low. Therefore, an alternative form is needed in developing student worksheet based virtual laboratory to train scientific attitudes as learning media as well as pre-lab facilities for students before starting practicum. This study aims to make LKPD based on virtual laboratory on photosynthetic material that is feasible in terms of validity, practicality, and effectiveness to train students' scientific attitudes. This research uses the 4D method (Define, Design, Develop, and Dissaminate) which has been tested on 25 class XII MIPA 7 of SMAN 1 Sampang. The results on the validity aspect have a percentage of 83.33% with the appropriate category, the practicality aspect based on the implementation of the LKPD was 85.58% and the readability was at level 12, and the effectiveness aspect based on student learning outcomes have a N-Gain score of 0.7472, activity observation results have 93%, and scientific attitude questionnaire have 84.21% with each category being very practical, high and very effective. Thus, the developed LKPD is considered feasible and effective for increasing scientific attitudes towards photosynthesis material.